THE EFFECT OF ACCOUNTING INFORMATION SYSTEMS AND THE FINANCING QUALITY ON PUBLIC HEALTH CENTER REMUNERATION SYSTEMS - Amien, Khonsa Mawadda; Adam, Helmy (Universitas Jember, 2024)
ABSTRACTThis study aims to analyze the effect of the Accounting Information System (AIS) and the Financing Management Quality on the Remuneration System Quality, involving samples of 53 Regional Public Service Agency of Public Health Centers (Puskesmas BLUD) in the former Ex. Regional of Madiun. This research is a quantitative study. The data were obtained from primary sources by distributing questionnaires and analyzed by Partial Least Square (PLS). The result of the study exhibit that the remuneration system quality at the BLUD Puskesmas can be affected by the accounting information system and the quality of financing management. Financing management system is proven to be able to mediate the influence of accounting information system on the remuneration system quality. As such, public health centers should consider this study to control the information comprehensiveness for the basis of employee remuneration.Keywords: Health Financing; Remuneration; Information System ABSTRAKPenelitian ini bertujuan untuk menganalisis pengaruh Sistem Informasi Akuntansi (SIA) dan Kualitas Manajemen Pembiayaan terhadap Kualitas Sistem Remunerasi pada Puskesmas yang telah berstatus Badan Layanan Umum Daerah (BLUD) di Eks Karesidenan Madiun. Sampel penelitian berjumlah 53 BLUD Puskesmas. Penelitian ini merupakan penelitian kuantitatif. Data penelitian diperoleh dari sumber primer melalui penyebaran kuesioner. Metode analisis data menggunakan Partial Least Square (PLS). Hasil penelitian ini adalah kualitas sistem remunerasi pada BLUD Puskesmas dapat dipengaruhi oleh sistem informasi akuntansi dan kualitas manajemen pembiayaan. Kualitas manajemen pembiayaan terbukti dapat memediasi pengaruh sistem informasi akuntansi terhadap kualitas sistem remunerasi. Penelitian ini dapat menjadi pertimbangan puskesmas untuk mengontrol kelengkapan informasi yang menjadi dasar penerimaan remunerasi pegawai.Kata Kunci: Pembiayaan Kesehatan; Remunerasi; Sistem Informasi